(untitled) (Journal of Humanities and Social Sciences Research, 2023)
Arab women have assumed an important social, economic and political status throughout the ages after long conflicts and struggles and a series of failures and successes to realize their rights as human beings, and in light of the new changes that societies have undergone in an era characterized by rapid real-time technological development and scientific progress, women’s practical, scientific, vital and influential contribution has become a fundamental necessity in all aspects of economic, social and politics. The research has reached important results, including: the need to work on spreading a culture of balance and equality between men and women, which is the basic principle for facing many challenges that stand as an obstacle towards empowering women, supporting their participation in development, and advancing the wheel of development in society. It is the main strong foundation for realizing all the rights that women seek to obtain in various aspects of life, as well as empowering women by the force of law, which is the strict hand of their support in entitlement to their rights, as many countries have put in place laws according to which women are empowered with compulsory education and Free to be a basic supporter of self-development for her children and building her community. The quota system that was created as a means to support women’s political empowerment with a limited positive impact is not reliable as a final goal with regard to the fairness of women’s political participation, since political parties’ choices for female candidates within the quota are not subject to the criteria of competencies and the appropriate scientific, cultural or popular level of well-earned achievements. Also, the dominance of tribal, clan and interest relations, where the capabilities of these female candidates are negated or have limited ability to absorb and present problems, solutions and sufferings of women, in order to reach positive legislation for those who represent them according to a mandatory political agenda that seeks to achieve it. The modern global standards brought about by the digital information revolution and its requirements in lifestyles necessitated their employment in creating mechanisms to empower women by preparing distinguished women not only within the educational level, but also with the expertise and skills that qualify them for leadership positions and active political participation and support them with all developmental means, especially with regard to the use of social media to educate women in order to change the stereotype set by the patriarchal culture and at the same time provide them with the skills and expertise necessary to qualify them scientifically, technically and politically to reach their primary role in community development through its political culture that qualifies them to build a better politician, a better social role model improving women political future.